Polymer additives, methods for producing the same, and polymer compositions containing the same
Patent Information
- Application Number
- JP2026042241
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-17
- Filing Date
- 2026-03-16
- Publication Date
- 2026-10-30
AI Technical Summary
Dialkylphosphinates used as flame retardants in polymers decompose at high temperatures, releasing acidic substances that cause mold deposits and water absorption, leading to decreased production efficiency and material degradation.
A production method involving the reaction of an aqueous hypophosphate solution with an antioxidant, controlled pH, and use of a flocculant to produce a polymer additive with low acid value and high thermal stability, reducing mold deposits and precipitates.
The polymer additive achieves low acidity and improved thermal stability, minimizing mold deposits and extending the service life of polymer compositions under humid conditions.
Abstract
Description
[Technical Field]
[0001] This invention belongs to the technical field of flame retardants, and more specifically, relates to additives for polymers, methods for producing the same, and polymer compositions containing the same. [Background technology]
[0002] Dialkylphosphinates are halogen-free, environmentally friendly, general-purpose flame retardants that offer excellent flame retardancy, require minimal additives, and have little impact on the physical and electrical properties of the base resin. More importantly, materials using dialkylphosphinates as flame retardants have characteristics such as a high CTI (relative tracking index) and low smoke generation during combustion, while also possessing excellent mechanical and electrical properties. As a result, they are becoming increasingly popular among manufacturers in the electrical and electronic equipment industry, and the market has great potential.
[0003] With the widespread application of dialkylphosphinates, significant performance defects have gradually been discovered. For example, research by Braun U et al. revealed that when dialkylphosphinates are used to flame retard PBT and polyamides, they decompose at high temperatures, releasing dialkylphosphinic acid. In particular, when dialkylphosphinates are used to flame retard polyamides, polyamides, which contain numerous polar amide groups, are relatively susceptible to water absorption and have a relatively high water absorption rate. For example, PA66 resin can have a water absorption rate of 2.7% under conditions of 23°C and 50% humidity. Dialkylphosphinates inherently possess a certain acidity during extrusion molding and high-temperature injection molding processes, and decompose during the heating process, releasing an acidic substance called dialkylphosphinic acid. As a result, the decomposition of the system is easily accelerated, and a large amount of gas is generated during processing. When injection molding is repeated multiple times, severe mold deposits often occur, not only significantly affecting the appearance of the product but also requiring frequent mold cleaning. Consequently, production efficiency decreases, making it difficult to effectively distribute and utilize the product.
[0004] Currently, the main method for solving the mold deposit problem in injection molding of polyamide materials flame-retardant with dialkylphosphinates is to add an acid absorbent to the system to lower its acidity. For example, EP2417191A1 discloses a halogen-free flame-retardant polyamide composition in which 0.15-1 wt% calcium oxide is added to neutralize some of the acidic substances in the system, thereby lowering the acidity of the system, reducing the decomposition of the matrix resin, and mitigating mold corrosion during high-temperature injection molding. While this method helps to reduce mold deposits to some extent, calcium oxide is highly hygroscopic, resulting in a relatively high water absorption rate in the system, making it difficult to control during processing.
[0005] The halogen-free flame-retardant thermoplastic polyamide composition disclosed in CN112409786A reduces the amount of mold deposit generated during the injection molding process by adding a certain amount of ethylene copolymer as an adsorbent. CN114874616A discloses that by introducing a composite system of metal oxides and polyhydroxy components into a halogen-free flame-retardant polyamide composite material, the manufactured polyamide material exhibits excellent resistance to yellowing, less mold deposit, and an increased number of mold openings and closings. While the above methods have some improvement effect on mold deposits in flame-retardant polyamides treated with dialkylphosphinates, both methods reduce mold deposits by improving the acidity of the system with external additives. This leads to increased costs and makes it difficult to avoid the effects of adding new substances on other properties of the flame-retardant polyamide. For example, the addition of inorganic metal oxides may lead to a decrease in the mechanical properties of the material. Furthermore, dialkylphosphinates themselves have insufficient heat resistance and exhibit significant weight loss at temperatures above 300°C, causing them to decompose during processing such as melt blending and extrusion, thus affecting their performance. Adding auxiliary agents externally does not fundamentally solve the problem of insufficient heat resistance of dialkylphosphinates.
[0006] Therefore, providing a flame retardant additive with relatively low acidity and better thermal stability, thereby reducing mold deposits in polymer compositions using it, and minimizing additive precipitation, is an urgent issue that needs to be addressed in the art. [Prior art documents] [Patent Documents]
[0007] [Patent Document 1] European Patent Application Publication No. 2417191 [Patent Document 2] Chinese Patent Application Publication No. 112409786 Specification [Patent Document 3] Chinese Patent Application Publication No. 114874616 [Overview of the Initiative] [Problems that the invention aims to solve]
[0008] The present invention aims to provide polymer additives, methods for producing the same, and polymer compositions containing the same, in order to address the shortcomings of the prior art. By designing and interacting the raw materials, process steps, and parameters in the production method, polymer additives with low acid value and high thermal stability can be obtained. When the polymer additive is used as a flame retardant in the production of a polymer composition, it can not only effectively reduce mold deposits but also reduce the content of precipitates when the polymer composition is boiled in water, thereby extending the service life of the polymer composition under humid heat conditions. [Means for solving the problem]
[0009] To achieve this objective, the present invention employs the following technical solutions.
[0010] In a first aspect, the present invention provides a method for producing polymer additives, the production method being: Step (1) involves reacting an aqueous hypophosphate solution with an antioxidant in the presence of an initiator to obtain an aqueous diethylphosphinate solution, Step (2) involves mixing the diethylphosphinate aqueous solution, the metal salt aqueous solution, and the alkaline solution, and reacting them under conditions of a pH of 3.5 to 3.8 to obtain a diethylphosphinate metal salt slurry. The process includes (3) mixing the diethylphosphinate metal salt slurry with a flocculant and stirring to obtain a diethylphosphinate metal salt aggregate, filtering the diethylphosphinate metal salt aggregate, washing and drying it to obtain the polymer additive.
[0011] Through research, the present invention has found that the water-soluble acid value and organic acid value of the product can be effectively reduced by adding an antioxidant in step (1). This is because the reaction between hypophosphite and ethylene is generally initiated by a free radical initiator. Since hypophosphite contains a pH bond, it has strong reducing properties. Therefore, in step (1), both a free radical reaction and an oxidation reaction occur simultaneously. The antioxidant introduced in the present invention can reduce the oxidizing agent to a more stable substance by donating electrons to the oxidizing agent. At the same time, the free radical reaction between hypophosphite and ethylene is a strong heat-releasing reaction, which is prone to uncontrollable phenomena during production and generates many side reactions. Therefore, by reacting with free radicals, the antioxidant captures the free radicals and neutralizes their activity, effectively mitigating the heat-releasing effect, reducing the occurrence of side reactions, and making the production process more controllable.
[0012] Furthermore, through research, the present invention has found that the pH of the reaction system significantly affects the crystallization behavior in the precipitation process of the additive, thereby affecting the acid value of the product. The present invention controls the pH value of the system in step (2) to 3.5-3.8, for example, 3.52, 3.55, 3.58, 3.6, 3.62, 3.65, 3.68, 3.7, 3.72, 3.75, 3.78, etc. Within this range, it is possible to produce a high-performance polymer additive that has a particularly low acid value and excellent heat resistance. When this polymer additive is used as a flame retardant in the manufacture of composite materials, the content of mold deposits and precipitates during boiling will be lower. If the pH value of the reaction system in step (2) is too low, the acidity of the polymer additive will become too high, and its thermal stability will tend to decrease. If the pH value of the reaction system is too high, the acid value of the polymer additive will also increase, further raising the pH value and reducing the yield.
[0013] Furthermore, the main function of the flocculant is to lower the potential of positively (negatively) charged groups and negatively (positively) charged granules or particles that are difficult to separate in water by taking advantage of their proximity, thereby creating an unstable state, and to collect these particles by utilizing their polymerization properties and separating them by physical or chemical methods. When the flocculant is used to floccate the polymer additive of the present invention, it fixes the surface of the polymer additive particles to the molecular chains of the flocculant through adsorption crosslinking and reinforcing action, forming polymer bridges, thereby causing the particles to floccate and settle. The flocculant can effectively improve the filtration and washing effects of the polymer additive by adsorbing and binding to the diethylphosphinate metal salt in the slurry obtained in step (2), and can also reduce the acidity of the polymer additive after filtration and washing.
[0014] As described above, the present invention particularly provides an improved method for producing an additive for polymers. By using an antioxidant and a flocculant in the production process and controlling the pH value in the metathesis reaction to 3.5 to 3.8, an additive for polymers having a low acid value and excellent thermal stability can be obtained. When the additive for polymers is used as a flame retardant in the production of a polymer composition, it can significantly reduce mold deposit, reduce the content of precipitates when the polymer composition is boiled in water, greatly improve the stability of the polymer composition under humid heat conditions, and extend the service life of the polymer composition.
[0015] The following are preferred technical solutions of the present invention, but they are not intended to limit the technical solutions of the present invention. The objects and beneficial effects of the present invention are better achieved and realized through the following preferred technical solutions.
[0016] Preferably, the hypophosphite includes sodium hypophosphite and / or potassium hypophosphite, and an aqueous solution of sodium diethylphosphinate and / or potassium diethylphosphinate obtained therefrom.
[0017] Furthermore, the hypophosphite may be anhydrous hypophosphite and / or hydrated hypophosphite.
[0018] Preferably, the hypophosphite is sodium hypophosphite, and the product obtained in step (1) is an aqueous solution of sodium diethylphosphinate.
[0019] Preferably, the mass fraction of hypophosphite in the aqueous hypophosphite solution is 10 to 60%, for example, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or 55%, and may be any specific value between the individual values listed above. However, in view of space limitations and brevity, the present invention does not list all specific values falling within the range. More preferably, it is 30 to 40%.
[0020] Preferably, the antioxidant includes one or a combination of at least two of the following: hindered amine antioxidants, hindered phenol antioxidants, phosphite antioxidants, and thioester antioxidants; more preferably, one or a combination of at least two of the following: hindered phenol antioxidants, phosphite antioxidants, and thioester antioxidants.
[0021] More preferably, the antioxidant includes one or a combination of at least two of the following: pentaerythritol tetrakis[3-[3,5-di(tert-butyl)-4-hydroxyphenyl]propionate] (antioxidant 1010), n-octadecyl-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate (antioxidant 1076), N,N'-bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hexamethylenediamine (antioxidant 1098), tris(2,4-di-tert-butylphenyl) phosphite (antioxidant 168), 2,6-di-tert-butyl-p-cresol (antioxidant BHT), β,β-distearylthiodipropionate (antioxidant DSTP), antioxidant 215, and antioxidant 225.
[0022] The antioxidant in the present invention may be a single component, for example, any one of the antioxidants listed above, or a composite antioxidant consisting of multiple components, for example, a combination of a hindered phenol antioxidant and a phosphite antioxidant. Typical combinations include formulations of antioxidant 1010 and antioxidant 168 in various ratios, such as antioxidant 215 and antioxidant 225.
[0023] Preferably, the mass ratio of the hypophosphate to the antioxidant is 100:(0.02~1.2), and may be, for example, 100:0.04, 100:0.05, 100:0.06, 100:0.08, 100:0.1, 100:0.2, 100:0.3, 100:0.4, 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:0.95, 100:1, 100:1.05, 100:1.1, or 100:1.15, but more preferably 100:(0.05~1).
[0024] Preferably, the initiator comprises one or a combination of at least two of the following: organic peroxides, persulfates, azo initiators, and photoinitiators.
[0025] Preferably, the organic peroxide is diisobutyryl peroxide, benzoyl peroxide, bis(2-ethylhexyl) peroxydicarbonate, diisopropyl peroxydicarbonate, 1,1,3,3-tetramethylbutyl peroxypivalate, tert-butyl peroxypivalate, t-amyl peroxypivalate, dilauroyl peroxide, di(3,3,5-trimethylacetyl) peroxide, 2,5-dimethyl-2,5-di(2-ethylacetylperoxy)hexane, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, di(4-methylbenzoyl) peroxide, tert-amyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2- This product contains one or at least two of the following: ethylhexanoate, tert-butylperoxyisobutyrate, 1,1'-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di-tert-amylperoxycyclohexane, 1,1-di(tert-butylperoxy)cyclohexane, di-tert-butylperoxide, di-tert-amylperoxide, dicumylperoxide, 2,5-di-tert-butylperoxy-2,5-dimethylhexane, tert-butylperoxyacetate, tert-amylperoxybenzoate, tert-butylperoxymaleate, and tert-butylperoxy 2-ethylhexyl carbonate.
[0026] Preferably, the persulfate comprises one or at least two of the following: sodium persulfate, potassium persulfate, and ammonium persulfate.
[0027] Preferably, the azo initiator includes one or at least two of the following: azobisisobutyronitrile, azobisisoheptanitrile, azobisisobutylamidine hydrochloride, 2,2-azobis[2-(2-imidazolin-2-yl)propane] hydrochloride, and 1-((cyano-1-methylethyl)azo)formamide.
[0028] In this invention, the specific selection of the photoinitiator is not particularly limited, and all photoinitiators commonly used in the art can be applied.
[0029] Furthermore, the initiator in step (1) of the present invention may be added all at once, in batches, or continuously during the reaction. In addition, in step (1), a portion of the initiator may be added in advance, and the remainder may be added continuously during the reaction process.
[0030] Preferably, the mass ratio of the hypophosphate to the initiator is 100:(0.1~5), and may be, for example, 100:0.2, 100:0.5, 100:1, 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5, 100:4, 100:4.5, or 100:4.8.
[0031] Preferably, the molar ratio of ethylene to hypophosphate is (2-2.1):1, and may be, for example, 2.01:1, 2.02:1, 2.04:1, 2.05:1, 2.06:1, 2.08:1, or 2.09:1.
[0032] Preferably, the temperature of the free radical reaction is 70 to 120°C, and may be a specific value between the above individual values, for example, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, or 115°C. However, for the sake of space and simplicity, this invention will not list all specific values within this range. More preferably, it is 80 to 110°C, and even more preferably, 90 to 105°C.
[0033] The free radical reaction in step (1) is carried out in the presence of an initiator, and when the pressure of the reaction system stops changing almost completely, the reaction is considered to be complete and the reaction is stopped.
[0034] Preferably, the free radical reaction is carried out in a protective atmosphere.
[0035] Preferably, the protective atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.
[0036] In the present invention, the metal salt in step (2) is a water-soluble metal salt, preferably the metal salt comprises a metal sulfate and / or a metal chloride, and more preferably a metal sulfate.
[0037] Preferably, the metal in the metal salt includes one or at least two of Al, Ca, Cu, Zn, Fe, and Ti, and more preferably Al.
[0038] Preferably, the metal salt contains aluminum sulfate.
[0039] The metal salt may be an anhydrous metal salt and / or a metal salt hydrate.
[0040] Preferably, the mass fraction of the metal salt in the aqueous solution of the metal salt is 20 to 40%, and may be a specific value between the above individual values, for example, 22%, 25%, 28%, 30%, 32%, 35%, or 38%. However, for the sake of space and clarity, this invention will not list all specific values that fall within this range.
[0041] Preferably, the molar ratio of the metal salt to the diethylphosphinate is 1:(5.8~6.2), and may be, for example, 1:5.82, 1:5.85, 1:5.88, 1:5.9, 1:5.92, 1:5.95, 1:5.98, 1:6, 1:6.02, 1:6.05, 1:6.08, 1:6.1, 1:6.12, 1:6.15, or 1:6.18, and more preferably 1:6.
[0042] Preferably, the alkaline solution comprises a sodium hydroxide solution and / or a potassium hydroxide solution.
[0043] In this invention, the mass concentrations of the sodium hydroxide solution and potassium hydroxide solution are not particularly limited, and it is sufficient that the pH of the reaction system obtained in step (2) can be maintained at 3.5 to 3.8 by adding the sodium hydroxide solution and / or potassium hydroxide solution.
[0044] Preferably, the temperature of the reaction in step (2) is 20 to 80°C, and may be a specific value between the above individual values, for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, or 75°C, but for the sake of space and simplicity, the present invention will not list all specific values that fall within this range. More preferably, it is 40 to 60°C.
[0045] Preferably, the reaction time in step (2) is 0.1 to 5 hours, and may be a specific value between the above individual values, such as 0.2 hours, 0.5 hours, 0.8 hours, 1 hour, 1.2 hours, 1.5 hours, 1.8 hours, 2 hours, 2.2 hours, 2.5 hours, 2.8 hours, 3 hours, 3.2 hours, 3.5 hours, 3.8 hours, 4 hours, or 4.5 hours. However, for the sake of space and clarity, the present invention will not list all specific values that fall within this range.
[0046] In step (2) of the present invention, the metal salt aqueous solution and the alkaline solution are added simultaneously to the diethylphosphinate aqueous solution and reacted, or the metal salt aqueous solution, the alkaline solution, and the diethylphosphinate aqueous solution are continuously added to a reaction apparatus (e.g., a stirring reaction vessel, a static mixer, a dynamic mixer) at a constant flow rate and thoroughly mixed and reacted. When the metal salt aqueous solution and the alkaline solution are added simultaneously to the diethylphosphinate aqueous solution and reacted, the reaction temperature is 20 to 80°C, preferably 30 to 70°C, and more preferably 40 to 60°C, and the dropwise addition time of the metal salt aqueous solution and the alkaline solution is 0.1 to 5 hours (e.g., 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, etc.), preferably 0.5 to 3 hours, and more preferably 1 to 3 hours. When an aqueous metal salt solution, an alkaline solution, and an aqueous diethylphosphinate solution are continuously added to a reaction vessel at a predetermined flow rate, the reaction temperature is 40 to 80°C, preferably 50 to 60°C, and the reaction space rate is 0.1 to 2 / h (e.g., 0.2 / h, 0.5 / h, 0.8 / h, 1 / h, 1.2 / h, 1.5 / h, 1.8 / h, etc.), preferably 0.3 to 1 / h, and more preferably 0.5 to 0.8 / h.
[0047] Preferably, the flocculant comprises one or at least two of the following: a polyacrylamide-based flocculant, a starch-based flocculant, and a chitin-based flocculant.
[0048] More preferably, the flocculant comprises anionic polyacrylamide and / or nonionic polyacrylamide.
[0049] As a preferred technical solution of the present invention, by using a polyacrylamide-based flocculant (preferably anionic polyacrylamide and / or nonionic polyacrylamide), the surface of the polymer additive particles can be fixed to the molecular chains of the flocculant, forming polymer bridges. In particular, when anionic polyacrylamide is added as a flocculant, it exhibits adsorption crosslinking and reinforcing effects, causing the particles to flocce and settle, improving the filtration and washing effects of the polymer additive, and reducing the acid value of the polymer additive after filtration and washing.
[0050] Preferably, with the theoretically obtained mass of the diethylphosphinate metal salt set to 100%, the mass of the flocculant is 0.01 to 0.5%, for example, 0.02%, 0.05%, 0.08%, 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, 0.22%, 0.25%, 0.28%, 0.3%, 0.32%, 0.35%, 0.38%, 0.4%, 0.42%, 0.45%, or 0.48%. Specific values between these individual values are also possible, but for the sake of space and clarity, this invention will not list all specific values within this range.
[0051] Here, the "theoretically obtained mass of the diethylphosphinate metal salt" is calculated based on the amounts of diethylphosphinate and metal salt added in step (2).
[0052] Preferably, first, the flocculant and water are mixed at 20-30°C for 10-20 minutes to obtain a flocculant solution, and then the flocculant solution and the diethylphosphinate metal salt slurry are mixed and stirred. Here, the mass ratio of the flocculant to water is 1:(10-1000), and may be, for example, 1:50, 1:100, 1:200, 1:300, 1:400, 1:500, 1:600, 1:700, 1:800, 1:900, or 1:950.
[0053] Preferably, the mixing temperature in step (3) is 40 to 60°C, and may be a specific value between the above individual values, for example, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, or 58°C. However, for the sake of space and simplicity, the present invention will not list all specific values that fall within this range.
[0054] Preferably, the number of washes in step (3) is ≥ 4, and may be, for example, 5, 6, 7, 8, 9, 10, or 12 times, and more preferably 5 to 10 times.
[0055] Preferably, the cleaning reagent used for the cleaning is water.
[0056] A preferred technical solution of the present invention is to filter the diethylphosphinate metal salt flocculant and then wash it multiple times, with the number of washes being ≥4, preferably 5 to 10 times. This allows for better removal of impurities and acidic substances from the product, resulting in a polymer additive with a low acid value and excellent thermal stability.
[0057] Preferably, in the washing, the mass ratio of water to solids is (1 to 10):1, independently of each other, and may be, for example, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, and more preferably (1.5 to 6):1. The solids are the solid products obtained by filtration.
[0058] Preferably, the drying temperature in step (3) is 105 to 250°C, and may be a specific value between the above individual values, for example, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 180°C, 200°C, 220°C, or 240°C, but for the sake of space and simplicity, the present invention will not list all specific values that fall within this range. More preferably, it is 110 to 150°C.
[0059] As a preferred technical solution of the present invention, the method for producing the polymer additive specifically includes the following steps.
[0060] (1) In a protective atmosphere, an aqueous solution of hypophosphate and an antioxidant are reacted with ethylene as a free radical agent to obtain an aqueous solution of diethylphosphinate.
[0061] Here, the mass fraction of hypophosphate in the hypophosphate aqueous solution is 10-60%, the mass ratio of hypophosphate, antioxidant, and initiator is 100:(0.02-1.2):(0.1-5), and the temperature of the free radical reaction is 70-120°C. The reaction stops when the pressure of the system no longer changes.
[0062] (2) The diethylphosphinate aqueous solution, the metal salt aqueous solution, and the alkaline solution are mixed and reacted under conditions of pH 3.5 to 3.8 and 40 to 60°C to obtain a diethylphosphinate metal salt slurry.
[0063] Here, the molar ratio of the metal salt to the diethylphosphinate is 1:(5.9~6.1), and the mass fraction of the metal salt in the aqueous solution of the metal salt is 20~40%.
[0064] (3) The diethylphosphinate metal salt slurry and the flocculant solution are mixed at 40-60°C and stirred to obtain a diethylphosphinate metal salt aggregate. The diethylphosphinate metal salt aggregate is filtered, washed ≥4 times, and dried to obtain the polymer additive.
[0065] Here, the theoretically obtained mass of the diethylphosphinate metal salt is set to 100%, and the mass of the flocculant is 0.01 to 0.5%.
[0066] In a second aspect, the present invention provides a polymer additive, which is manufactured by the manufacturing method described in the first aspect, and the water-soluble acid value of the polymer additive is ≤0.33 mg KOH / g. The polymer additive comprises, in parts by mass, the following components: 96-99.88 parts of diethylphosphinate, 0.1 to 2 parts of ethylbutylphosphinate, 0.01 to 1 part of ethylphosphonate, It contains 0.01 to 1 part of monoethylphosphinate.
[0067] The polymer additive according to the present invention has a low acid value and excellent thermal stability, with a water-soluble acid value of ≤0.33 mg KOH / g. When used as a flame retardant in a polymer composition, it suppresses the release of dialkylphosphinic acid due to high-temperature decomposition, reduces the content of precipitates when the polymer composition is boiled in water, improves the stability of the polymer composition under humid heat conditions, extends the service life, and further reduces the amount of mold deposit generated during injection molding.
[0068] In the polymer additive described above, the amount of diethylphosphinate is 96 to 99.88 parts by mass, and may be, for example, 96 parts, 96.2 parts, 96.5 parts, 96.8 parts, 96.9 parts, 97 parts, 97.2 parts, 97.5 parts, 97.8 parts, 98 parts, 98.2 parts, 98.5 parts, 98.8 parts, 99 parts, 99.2 parts, 99.5 parts, 99.6 parts, or 99.8 parts. However, for the sake of space and clarity, the present invention will not list all specific values within this range.
[0069] Preferably, in the polymer additive, the mass fraction of diethylphosphinate is ≥95%, and may be a specific value between the above individual values, such as 95.5%, 96%, 96.2%, 96.5%, 96.8%, 97%, 97.2%, 97.5%, 97.8%, 98%, 98.2%, 98.5%, 98.8%, 99%, 99.2%, 99.5%, 99.8%, or 99.88%. However, for the sake of space and clarity, the present invention will not list all specific values within this range.
[0070] In the polymer additive, the amount of ethylbutylphosphinate is 0.1 to 2 parts by mass, and may be, for example, 0.12 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts, or 1.8 parts, or any specific value between the above individual values. However, for the sake of space and clarity, the present invention will not list all specific values within this range.
[0071] In the polymer additive, the amount of ethylphosphonate by mass is 0.01 to 1 part, and may be, for example, 0.02 parts, 0.05 parts, 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts, 0.4 parts, 0.45 parts, 0.5 parts, 0.55 parts, 0.6 parts, 0.65 parts, 0.7 parts, 0.75 parts, 0.8 parts, 0.85 parts, 0.9 parts, or 0.95 parts, or any specific value between the above individual values. However, for the sake of space and clarity, the present invention will not list all specific values included in this range.
[0072] In the polymer additive described above, the amount of monoethylphosphinate is 0.01 to 1 part by mass, and may be, for example, 0.02 parts, 0.05 parts, 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts, 0.4 parts, 0.45 parts, 0.5 parts, 0.55 parts, 0.6 parts, 0.65 parts, 0.7 parts, 0.75 parts, 0.8 parts, 0.85 parts, 0.9 parts, or 0.95 parts. However, for the sake of space and clarity, the present invention will not list all specific values within this range.
[0073] For example, the mass parts of diethylphosphinate, ethylbutylphosphinate, ethylphosphonate, and monoethylphosphinate in the polymer additive can be analyzed and tested by liquid chromatography. For instance, a test sample is dissolved in a 5:1 aqueous sulfuric acid solution (30% by mass) relative to the sample's mass, and then diluted 10 to 30 times in the mobile phase for analysis. The mobile phase is a mixture of water and methanol in a mass ratio of 9:1, to which 0.5% trifluoroacetic acid is added by volume. A ShimNex CS C18 column is used, with a flow rate of 0.6 mL / min. The mass fraction of each component is calculated by area normalization.
[0074] Preferably, in the polymer additive, the mass of the other phosphorus-containing compound is ≤ 1.2 parts, and may be a specific value between the above individual values, such as 0, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, or 1.1 parts. However, for the sake of space and clarity, the present invention will not list all specific values within this range. More preferably, it is 0.05 to 0.9 parts.
[0075] The other phosphorus-containing compounds are alkali-soluble and phosphorus-containing substances other than diethylphosphinate, ethylbutylphosphinate, ethylphosphonate, and monoethylphosphinate. Their mass can be obtained by phosphorus nuclear magnetic spectroscopy, and in the phosphorus nuclear magnetic spectrum, the integrated area of the peaks other than diethylphosphinate, ethylbutylphosphinate, ethylphosphonate, and monoethylphosphinate represents the content of the other phosphorus-containing compounds.
[0076] Preferably, the polymer additive comprises, in parts by mass, as a component: 97.7 to 99 parts of diethylphosphinate, 0.5 to 0.7 parts of ethylbutylphosphinate and 0.1 to 0.5 parts of ethylphosphonate and comprises 0.1 to 0.7 parts of monoethylphosphinate.
[0077] Preferably, the cations of said diethylphosphinate, ethylbutylphosphinate, ethylphosphonate and monoethylphosphinate are the same, and are Al 3+ , Ca 2+ , Cu 2+ , Zn 2+ , Fe 2+ , Fe 3+ , or Ti 4+ , any one selected from the foregoing or a combination of at least two kinds.
[0078] In the present invention, the water-soluble acid value of the polymer additive is ≤ 0.33 mg KOH / g, for example, may be 0.01 mg KOH / g, 0.1 mg KOH / g, 0.12 mg KOH / g, 0.15 mg KOH / g, 0.18 mg KOH / g, 0.2 mg KOH / g, 0.22 mg KOH / g, 0.25 mg KOH / g, 0.28 mg KOH / g, 0.29 mg KOH / g, 0.3 mg KOH / g, 0.31 mg KOH / g or 0.32 mg KOH / g, and may be any specific value falling between the individual values listed above; however, in view of space limitations and for brevity, the present invention does not enumerate all specific values included in said range. Preferably, it is 0.1 to 0.3 mg KOH / g.
[0079] Illustratively, the water-soluble acid value of the polymer additive can be measured by the following method. 1 g of a test sample is uniformly wetted with ethanol (the mass of ethanol is m エタノール ), then water (the mass of water is m 水 ) is added, after boiling in water at 90°C for 1 h in a sealed state, the mixture is cooled to 25°C, kept warm for 30 min, and water is supplemented until the total mass reaches the total mass before boiling. After filtration, a transparent filtrate with a mass of m1 is obtained. The test acid value of the transparent filtrate is measured by potentiometric titration. Wherein, the concentration of the potassium hydroxide solution used for titration is 0.05 mol / L, and the water-soluble acid value of the polymer additive = test acid value × (m 水 + m エタノール ) / m1.
[0080] Preferably, the organic acid value of the polymer additive is ≤0.05 mg KOH / g, and may be, for example, 0.001 mg KOH / g, 0.005 mg KOH / g, 0.01 mg KOH / g, 0.02 mg KOH / g, 0.022 mg KOH / g, 0.025 mg KOH / g, 0.028 mg KOH / g, 0.03 mg KOH / g, 0.032 mg KOH / g, 0.035 mg KOH / g, 0.038 mg KOH / g, 0.04 mg KOH / g, or 0.045 mg KOH / g. However, for the sake of space and clarity, this invention will not list all specific values within this range. More preferably, it is 0.002 to 0.04 mg KOH / g.
[0081] For example, the organic acid value of the polymer additive can be measured by the following method: 1 g of the test sample is mixed with dichloromethane (the mass of dichloromethane is m). ジクロロメタン The mixture is uniformly moistened with ), boiled in 90°C water for 1 hour in a sealed state, then cooled to 25°C, kept warm for 30 minutes, and dichloromethane is added until the total mass is equal to the mass before boiling. The mixture is filtered to obtain a clear filtrate of mass m1. The test acid value of the clear filtrate is measured by potentiometric titration. Here, the concentration of the potassium hydroxide solution used in the titration is 0.05 mol / L, and the organic acid value of the polymer additive = test acid value × m ジクロロメタン It is / m1.
[0082] Preferably, the mass fraction of sulfate in the polymer additive is 100 to 600 ppm, and may be a specific value between the above individual values, such as 120 ppm, 150 ppm, 200 ppm, 250 ppm, 270 ppm, 300 ppm, 350 ppm, 400 ppm, 420 ppm, 450 ppm, 500 ppm, 550 ppm, or 580 ppm. However, for the sake of space and clarity, this invention will not list all specific values within this range. More preferably, it is 110 to 370 ppm.
[0083] For example, the mass fraction of sulfate in the polymer additive is measured by an external standard method using ion chromatography, referring to the method of EN 14582:2007 standard "Measurement of halogen content".
[0084] Preferably, the 1% thermal loss temperature of the polymer additive is ≥ 350°C, and may be a specific value between the above individual values, such as 355°C, 358°C, 360°C, 362°C, 365°C, 368°C, 370°C, 372°C, 375°C, 378°C, 382°C, or 385°C. However, for the sake of space and clarity, this invention will not list all specific values within this range. More preferably, it is 358 to 380°C.
[0085] In this invention, the term "1% thermal weight loss temperature" refers to the temperature at which the weight of a polymer additive decreases by 1% under heating conditions, and can be tested in an air atmosphere using a thermogravimetric analyzer (TGA).
[0086] Preferably, the polymer additive D 50 The particle size is 1 to 100 μm, and may be, for example, 10 μm, 20 μm, 30 μm, 33 μm, 35 μm, 38 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, or 95 μm, or a specific value between the above individual values. However, for the sake of space and clarity, this invention will not list all specific values within this range. More preferably, the particle size is 20 to 60 μm, and even more preferably, 33 to 39 μm.
[0087] The polymer additive D 50 The particle size is the particle size corresponding to the cumulative volume distribution ratio of 50%, and can be measured using a laser particle size analyzer, referring to the particle size distribution laser diffraction method in the standard GB / T 19077-2016.
[0088] Preferably, the water content of the polymer additive is 0.01 to 1 wt%, and may be a specific value between the above individual values, such as 0.02 wt%, 0.05 wt%, 0.08 wt%, 0.1 wt%, 0.15 wt%, 0.2 wt%, 0.25 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, or 0.9 wt%, but for the sake of space and clarity, the present invention will not list all specific values within this range. More preferably, it is 0.05 to 0.3 wt%, and even more preferably, 0.1 to 0.25 wt%.
[0089] For example, the water content of the polymer additive can be measured using an infrared moisture analyzer. For instance, using the MA 35 infrared moisture analyzer manufactured by Sartorius GmbH in Germany, the water content is automatically measured after the sample has been left at 120°C for 30 minutes.
[0090] Preferably, the phosphorus content of the polymer additive is 22-25 wt%, and may be specific values between the above individual values, such as 22.2 wt%, 22.5 wt%, 22.8 wt%, 23 wt%, 23.2 wt%, 23.5 wt%, 23.8 wt%, 24 wt%, 24.2 wt%, 24.5 wt%, or 24.8 wt%, but for the sake of space and clarity, this invention will not list all specific values within this range. More preferably, it is 23-24 wt%.
[0091] For example, the phosphorus content of the polymer additive can be measured by the following method: Dissolve the test sample in an aqueous sulfuric acid solution (30% by mass) and measure it according to standard GB / T 11893-1989 "Water Quality: Measurement of Total Phosphorus - Ammonium Molybdate Spectrophotometric Method".
[0092] In a third aspect, the present invention provides the use of the polymer additive described in the second aspect in a polymer material.
[0093] Preferably, the polymer additive is applied to the polymer material as a flame retardant.
[0094] Preferably, the polymer material comprises one or at least two of the following: polyamide, polyester, polyurethane, styrene polymer, polyolefin, polyphenylene ether, and polyacrylate, and more preferably, polyamide and / or polyester.
[0095] In a fourth aspect, the present invention provides a polymer composition comprising a polymer matrix and a polymer additive as described in the second aspect.
[0096] Preferably, the polymer composition comprises, in parts by mass, as a component: Polymer matrix 40-99 parts, The polymer additive comprises 5 to 35 parts of the above-mentioned polymer additive.
[0097] Preferably, the amount of the polymer matrix is 40 to 99 parts by mass, and may be a specific value between the above individual values, such as 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 98 parts. However, for the sake of space and clarity, this invention will not list all specific values that fall within this range.
[0098] Preferably, the amount of the polymer additive is 5 to 35 parts by mass, and may be a specific value between the above individual values, such as 6, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30, 32, or 34 parts. However, for the sake of space and clarity, this invention will not list all specific values within this range.
[0099] Preferably, the polymer matrix comprises polyamide and / or polyester.
[0100] Preferably, the polyamide includes one or at least two of the following: a polyamide resin or a polyamide elastomer.
[0101] The polyamide includes one or a combination of at least two of the following: condensation products of dicarboxylic acids and diamines, condensation products of ω-amino acids, and ring-opening polymerization products of cyclic lactams. The dicarboxylic acid includes, but is not limited to, one or a combination of at least two of the following: adipic acid, sebacic acid, dodecanediic acid, terephthalic acid, and isophthalic acid. Examples of the diamine include, but are not limited to, one or a combination of at least two of the following: pentanediamine, hexamethylenediamine, decanediamine, dodecanediamine, butanediamine, p-phenylenediamine, and m-phenylenediamine. Examples of the cyclic lactam include, but are not limited to, one or a combination of at least two of the following: caprolactam, capryloractam, undecalactam, and laurolactam. Examples of the aforementioned ω-amino acids include, but are not limited to, one or at least two of the ω-amino acids formed by the ring-opening of the aforementioned cyclic lactams and aminobenzoic acids.
[0102] Preferably, the polyamide includes one or at least two of the following: polyamide 6 (polycaprolactam), polyamide 11 (polyundecalactam), polyamide 12 (polylaurolactam), polyamide 56 (polypentamethylene adipamide), polyamide 66 (polyhexamethylene adipamide), polyamide 610 (polyhexamethylene sevacamide), polyamide 612 (polyhexamethylene dodecamide), polyamide 1010 (polydecamethylene sevacamide), polyamide 1012 (polydecamethylene dodecamide), polyamide 1212 (polydodecamethylene dodecamide), polyamide 6T (polyhexamethylene terephthalamide), polyamide 10T (polydecamethylene terephthalamide), and PPA (polyphthalamide).
[0103] Preferably, the polyester comprises a condensation product of a dicarboxylic acid and / or its derivative and a diol. Examples of the dicarboxylic acid include, but are not limited to, one or at least two of terephthalic acid, isophthalic acid, phthalic acid, succinic acid, adipic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, cyclohexanedicarboxylic acid, hydrogenated isophthalic acid, and hydrogenated phthalic acid. Derivatives include acid halides (acid chlorides), esters, and acid anhydrides formed from the dicarboxylic acid. Examples of the diol include, but are not limited to, ethylene glycol, butanediol, and hexanediol, one or at least two of them.
[0104] Exemplary examples include polyethylene terephthalate (PET) and / or polybutylene terephthalate (PBT).
[0105] Furthermore, the polymer composition of the present invention may also include other additives and auxiliaries intended to be added in the art.
[0106] Preferably, the polymer composition further includes a reinforcing agent and / or a filler.
[0107] Preferably, the reinforcing material includes glass fibers and / or carbon fibers.
[0108] Preferably, in the polymer composition, the parts by mass of the reinforcing material is ≤ 45 parts, and the parts by mass of the reinforcing material may be 0, 0.5, 1, 2, 5, 8, 10, 15, 20, 25, 30, 35, 40, 42, or 44 parts, or any specific value between the above individual values. However, for the sake of space and clarity, the present invention will not list all specific values that fall within this range.
[0109] Preferably, the filler includes one or at least two of the following: silica, talc powder, titanium dioxide, barium sulfate, kaolin, calcium sulfate, boehmite, mica, magnesium carbonate, and glass beads.
[0110] Preferably, in the polymer composition, the parts by mass of the filler is ≤40 parts, and the parts by mass of the filler may be 0, 0.5, 1, 2, 5, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30, 32, 35, or 38 parts, or any specific value between the above individual values. However, for the sake of space and clarity, the present invention will not list all specific values that fall within this range.
[0111] Preferably, the polymer composition further comprises 0 to 15 parts by mass of other additives, the amount of which may be 0, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, or 14 parts by mass, or any specific value between the above individual values. However, for the sake of space and clarity, the present invention will not list all specific values within this range.
[0112] Preferably, the other additives include one or a combination of at least two of the following: antioxidants, ultraviolet absorbers, lubricants, nucleating agents, stabilizers, antistatic agents, and colorants.
[0113] Preferably, the polymer composition further comprises one or a combination of at least two of the following: antioxidants, ultraviolet absorbers, lubricants, nucleating agents, stabilizers, antistatic agents, and colorants.
[0114] Preferably, in the polymer composition, the parts by mass of the antioxidant, ultraviolet absorber, lubricant, and nucleating agent are each independently 0.01 to 1.5 parts, for example, 0.05 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, 1.2 parts, or 1.4 parts, or any specific value between the above individual values. However, for the sake of space and clarity, the present invention will not list all specific values within this range.
[0115] Preferably, the antioxidant in the polymer composition includes one or at least two of the following: a hindered amine antioxidant, a hindered phenol antioxidant, a phosphite antioxidant, and a thioester antioxidant.
[0116] For example, the antioxidants in the polymer composition are pentaerythritol tetrakis[3-[3,5-di(tert-butyl)-4-hydroxyphenyl]propionate] (antioxidant 1010), n-octadecyl-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate (antioxidant 1076), and N,N'-bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hexamethylenediamine ( It contains one or at least two of the following antioxidants: antioxidant 1098), tris(2,4-di-tert-butylphenyl) phosphite (antioxidant 168), bis(2,4-di-tert-phenyl)pentaerythritol diphosphite (antioxidant 608), 2,6-di-tert-butyl-p-cresol (antioxidant BHT), β,β-distearyl thiodipropionate (antioxidant DSTP), antioxidant 215, and antioxidant 225.
[0117] Preferably, the lubricant includes one or at least two of the following: ester-based lubricants, alcohol-based lubricants, hydrocarbon-based lubricants, fatty acid-based lubricants, fatty acid amide-based lubricants, and metal soap-based lubricants.
[0118] Preferably, the polymer composition further comprises 0 to 15 parts by mass of a synergistic flame retardant, the amount of which may be 0, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, or 14 parts by mass, or any specific value between the above individual values. However, for the sake of space and clarity, the present invention will not list all specific values within this range.
[0119] Preferably, the synergistic flame retardant comprises one or at least two of the following: melamine polyphosphate, melamine polyphosphate salt, zinc borate, zinc stannate, zinc sulfide, and boehmite.
[0120] In one preferred technical solution, the polymer composition comprises, in parts by mass, as a component, Polymer matrix 40-99 parts, The polymer additive 5 to 35 parts, Reinforcement material 0-45 parts, Synergistic flame retardant 0-15 parts, Lubricant 0-1.5 parts, Contains 0 to 1.5 parts of antioxidant.
[0121] Preferably, in the polymer composition, the mass fraction of the polymer matrix is 40% to 99%, and may be a specific value between the above individual values, for example, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 98%. However, for the sake of space and clarity, the present invention will not list all specific values that fall within this range.
[0122] Preferably, in the polymer composition, the mass fraction of the polymer additive is 5% to 35%, and may be a specific value between the above individual values, such as 6%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, or 34%. However, for the sake of space and clarity, the present invention will not list all specific values within this range. More preferably, it is 6% to 20%.
[0123] Exemplary, a method for producing the polymer composition includes the steps of melting and blending the components of the polymer composition, and then extruding them to obtain the polymer composition.
[0124] Preferably, the molten blend is carried out in a screw extruder.
[0125] Preferably, the screw extruder is a twin-screw extruder.
[0126] Preferably, the temperature of the screw extruder is 180 to 330°C, and may be a specific value between the above individual values, such as 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, or 320°C. However, for the sake of space and clarity, the present invention will not list all specific values within this range.
[0127] Preferably, the process further includes granulation and drying steps after the extrusion. [Effects of the Invention]
[0128] Compared to the prior art, the present invention has the following beneficial effects.
[0129] The method for producing polymer additives according to the present invention allows for the production of polymer additives with low acid value and high thermal stability through the design and interaction of materials such as antioxidants and flocculants, process steps, and parameters. When the polymer additive is used as a flame retardant in the production of a polymer composition, it is possible to effectively reduce mold deposits generated during injection molding, reduce the content of precipitates when the polymer composition is boiled in water, significantly improve the stability of the polymer composition under humid heat conditions, and extend its service life. [Modes for carrying out the invention]
[0130] The technical solutions of the present invention will be further described below through specific embodiments. Those skilled in the art should understand that the described embodiments are merely intended to facilitate understanding of the present invention and should not be construed as limiting the invention in any way.
[0131] The terms “include,” “contain,” “have,” “contain,” or any other variations thereof used herein are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus containing the enumerated elements is not limited to those elements and may also contain other elements not expressly enumerated, or elements specific to such composition, step, method, article, or apparatus.
[0132] In the following specific embodiments, the test method for the parameters of the polymer additive is as follows: (1) Testing of the content of diethylphosphinate, ethylbutylphosphinate, ethylphosphonate, and monoethylphosphinate
[0133] The analysis and testing will be performed using a liquid chromatograph (LC20A, Shimadzu Corporation, Japan). Of these, diethylphosphinate will be used as a commercially available standard sample, ethylbutylphosphinate as a pure standard sample (prepared according to Example 4 of CN103172668A), ethylphosphonate as a pure standard sample (prepared according to Example 2 of CN104371142A), and monoethylphosphinate as a pure standard sample (prepared according to Example 1 of CN103172668A). The test sample will be dissolved in a 5:1 volume of sulfuric acid aqueous solution (30% by mass), then diluted 20-fold in the mobile phase, and analyzed and tested. The mobile phase will be a mixture of water and methanol in a mass ratio of 9:1, to which 0.5% trifluoroacetic acid by volume will be added. A ShimNex CS C18 5μm, 4.6×250mm column will be used, and the flow rate will be 0.6 mL / min. The mass fraction of each component is calculated using the area normalization method. (2) Content of other phosphorus-containing compounds
[0134] The test sample is mixed with a deuterated aqueous solution of deuterated sodium hydroxide (mass concentration 10%) in a mass ratio of 1:30 to completely dissolve the sample. After filtration, the resulting clear liquid is subjected to a magnetic resonance spectrometer (NMR, Bruker AVANCE NEO 400 MHz) to measure the phosphorus nuclear magnetic spectrum. The phosphorus nuclear magnetic spectrum is integrated, and the percentage of the integrated area of peaks other than the known diethylphosphinate, ethylbutylphosphinate, ethylphosphonate, and monoethylphosphinate is defined as the content of the other phosphorus-containing compounds. (3) Water-soluble acid value
[0135] Take 1 g of the test sample and measure 5.00 ± 0.01 g (m エタノール Add ethanol to the mixture and moisten evenly, then add 50±0.01g(m 水 Add room temperature water () and weigh the total weight m0 while stirring the bottle. Boil in 90°C water for 1 hour in a sealed state, then cool to 25°C and keep warm for 30 minutes. Add water until the total weight is m0. Filter to obtain a clear filtrate of mass m1. Measure the test acid value of the clear filtrate by potentiometric titration. The concentration of the potassium hydroxide solution used in the titration was 0.05 mol / L, and the water-soluble acid value of the polymer additive = test acid value × (m 水 +m エタノール ) / m1. (4)Organic acid value
[0136] Take 1 g of test sample and measure 50.0 ± 0.01 g (m ジクロロメタン Add the dichloromethane to the solution, moisten it uniformly, and weigh the total weight m0 while stirring the bottle. Boil in 90°C water for 1 hour in a sealed state, then cool to 25°C and keep warm for 30 minutes. Replenish with dichloromethane until the total weight reaches m0. Filter to obtain a clear filtrate with mass m1. Measure the test acid value of the clear filtrate by potentiometric titration. The concentration of the potassium hydroxide solution used in the titration was 0.05 mol / L, and the organic acid value of the polymer additive = test acid value × m ジクロロメタン It is / m1. (5) Mass fraction of sulfate
[0137] The measurement is performed by an external standard method employing ion chromatography techniques, referring to the method described in standard EN 14582:2007 - "Measurement of halogen content". (6)D 50 particle size
[0138] A 0.1g test sample is taken, moistened with 5g of ethanol, diluted with 50mL of water, and tested using a Mastersizer 3000 laser particle size distribution analyzer. (7) Moisture content
[0139] The test sample is placed in an infrared moisture analyzer (MA 35, Sartorius, Germany), left at 105°C for 30 minutes, and then the moisture content is automatically measured. (8) Phosphorus content
[0140] A 0.1g test sample is taken, dissolved in 2g of sulfuric acid aqueous solution (mass concentration 30%), and measured according to standard GB / T 11893-1989 "Water Quality: Measurement of Total Phosphorus - Ammonium Molybdate Spectrophotometric Method". (9)1% heat loss temperature
[0141] A 10 mg test sample is taken and measured using a thermogravimetric analyzer (TGA, NETZSCH TG 209 F3, Germany). The heating rate is 20°C / min, the protective gas is nitrogen, and the purge gas is air. The temperature corresponding to a 1% weight loss is measured.
[0142] In the following specific embodiments of the present invention, all materials for which preparation methods are not shown are commercially available chemicals. Specific information regarding some of the materials is as follows:
[0143] TIFF2026153789000001.tif103160
[0144] The polymer additive and its manufacturing method of the present invention will be described in detail below with reference to several examples, but the polymer additive and its manufacturing method are not limited to these examples. Examples 1-11, Comparative Examples 1-4
[0145] A polymer additive and a method for producing the same, wherein the production method is as follows: (1) 31.8 kg of solid sodium hypophosphite monohydrate, 50 kg of water, 500 g of sodium persulfate, antioxidant 1010 by mass m1, and antioxidant 168 by mass m2 were placed in a high-pressure vessel, nitrogen purging was performed three times, ethylene was maintained at 1.5 MPa using a depressurizer, heated to 95°C, and kept warm for 4 hours. 2500 g of a 20% mass fraction sodium persulfate aqueous solution was continuously added during the 4-hour warming period, and then kept warm at 95°C for 1 hour, cooled and evacuated to obtain an aqueous sodium diethylphosphinate solution. (2) The aqueous solution of sodium diethylphosphinate obtained in step (1) was diluted until the mass fraction of sodium diethylphosphinate was 20% (containing 6 mol of sodium diethylphosphinate), heated to a temperature T1, and within 1 hour, an aqueous solution of aluminum sulfate (containing 1 mol of aluminum sulfate, with a mass fraction of 28%) was continuously added dropwise, and the pH value was adjusted with potassium hydroxide solution (mass fraction of 5%) to obtain an aluminum diethylphosphinate slurry. (3) Add an aqueous solution of flocculant prepared with m³ by mass of anionic polyacrylamide and 50 g of water to the aluminum diethylphosphinate slurry obtained in step (2) at 50°C, stir until flocculated, filter, wash the filtered cake five times with three times its mass of water, and dry at 110°C until it reaches a predetermined weight to obtain a polymer additive.
[0146] The specific process parameters of the manufacturing method and the relevant data for the manufactured polymerization additives are shown in Tables 1 and 2.
[0147] [Table 1]
[0148] [Table 2]
[0149] As can be seen from Table 1, the present invention provides a method for producing polymer additives. In particular, by using antioxidants and flocculants and controlling the pH value in the metathesis reaction system in step (2), polymer additives with low acid value and high thermal stability were obtained. The water-soluble acid value is ≤0.33 mg KOH / g, and the 1% thermal weight loss temperature is ≥350°C. The polymer additive contains, by mass, 96 to 99.88 parts of diethylphosphinate, 0.1 to 2 parts of ethylbutylphosphinate, 0.01 to 1 part of ethylphosphonate, and 0.01 to 1 part of monoethylphosphinate as components.
[0150] In Table 2, the pH value of the reaction system in step (2) of Comparative Examples 1 and 2 exceeded the range of 3.5 to 3.8 limited in the present invention. In Comparative Example 3, no antioxidant was used, and in Comparative Example 4, no flocculant was added, resulting in a significant increase in both the water-soluble acid value and the organic acid value of the polymer additive, a decrease in the 1% heat loss temperature, and a decrease in thermal stability.
[0151] The use of the polymer additives described in the present invention will be explained in detail below using application examples, but the use of the polymer additives is not limited to these application examples. Application Examples 1-11, Comparative Application Examples 1-4
[0152] In polymer compositions, specifically polyamide compositions, the types and amounts of each component used are shown in Tables 3 and 4, and the unit of measurement for the amount of each component used is "parts by mass".
[0153] The method for producing the polyamide composition includes the steps of: mixing polyamide 66, polyamide 6, glass fiber, polymer additives, antioxidants, and lubricants in proportion to obtain a premix; and adding the premix to a twin-screw extruder, setting the screw rotation speed of the twin-screw extruder to 380 rpm, and the temperatures of zones 1 to 12 to 90°C, 180°C, 260°C, 250°C, 230°C, 230°C, 220°C, 220°C, 220°C, 220°C, 260°C, and 260°C respectively, melting and mixing, extruding and granulating to obtain polyamide composition particles.
[0154] The following performance tests were performed on the polyamide composition.
[0155] (1) Test for phosphorus content during boiling: 50 g of polyamide composition particles were added to 500 mL of hot water at 90°C, boiled for 1 hour, cooled to room temperature, filtered, and the phosphorus content in the filtrate was measured using the ammonium molybdate spectrophotometric method described in GB / T 11893-1989.
[0156] (2) Test method for mold deposits: Using an injection molding machine, polyamide composition particles were continuously injection molded into 150 molds at injection temperatures of 290°C, 285°C, 280°C, and 260°C. The mold deposit sample from the last mold was taken out and weighed using an analytical balance. The data for each test are shown in Tables 3 and 4.
[0157] [Table 3]
[0158] [Table 4]
[0159] As can be seen from the data in Tables 3 and 4, when the polymer additive according to the present invention is used as a flame retardant in a polyamide composition, it significantly reduces the amount of mold deposit generated during injection molding, bringing the mold deposit to ≤8.0 mg, and the phosphorus content of the polyamide composition when boiled in water to ≤527 ppm, thereby reducing the amount of precipitates when boiled in water, improving the stability of the polyamide composition under moist heat conditions, and extending its service life.
[0160] As can be seen from the test data in Table 4, the polymer additives in Comparative Examples 1 to 4 had high acid values and poor thermal stability. As a result, when used as flame retardants in polyamide compositions, they produced a large amount of mold deposits, high phosphorus content during boiling, and insufficient stability under humid heat conditions.
[0161] The applicant states that while the present invention illustrates the polymer additives of the present invention, methods for producing the same, and polymer compositions containing the same through the above examples, the present invention is not limited to the above examples, i.e., it does not mean that one must rely on the above examples to carry out the present invention. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of each raw material in the product of the present invention, addition of auxiliary components, selection of specific methods, etc., are all included within the scope of protection and disclosure of the present invention.
Claims
1. A method for producing additives for polymers, wherein the production method is: Step (1) involves reacting an aqueous hypophosphate solution with an antioxidant and ethylene in the presence of an initiator to obtain an aqueous diethylphosphinate solution, Step (2) involves mixing the diethylphosphinate aqueous solution, the metal salt aqueous solution, and the alkaline solution, and reacting them under conditions of a pH of 3.5 to 3.8 to obtain a diethylphosphinate metal salt slurry. A method for producing a polymer additive, comprising the steps of (3) mixing the diethylphosphinate metal salt slurry with a flocculant and stirring to obtain a diethylphosphinate metal salt aggregate, filtering the diethylphosphinate metal salt aggregate, washing and drying it to obtain the polymer additive.
2. The hypophosphate comprises sodium hypophosphate and / or potassium hypophosphate. Preferably, the mass fraction of hypophosphate in the hypophosphate aqueous solution is 10 to 60%, more preferably 30 to 40%. Preferably, the antioxidant includes one or a combination of at least two of the following: hindered amine antioxidants, hindered phenol antioxidants, phosphite antioxidants, and thioester antioxidants; more preferably, it includes one or a combination of at least two of the following: hindered phenol antioxidants, phosphite antioxidants, and thioester antioxidants. Preferably, the antioxidant comprises one or at least two of the following: pentaerythritol tetrakis[3-[3,5-di(tert-butyl)-4-hydroxyphenyl]propionate], n-octadecyl-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, N,N'-bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hexamethylenediamine, tris(2,4-di-tert-butylphenyl)phosphite, 2,6-di-tert-butyl-p-cresol, and β,β-distearylthiodipropionate. The manufacturing method according to claim 1, characterized in that, preferably, the mass ratio of the hypophosphate to the antioxidant is 100:(0.02 to 1.2), and more preferably, 100:(0.05 to 1).
3. The initiator comprises one or at least two of the following: organic peroxides, persulfates, azo initiators, and photoinitiators. Preferably, the mass ratio of the hypophosphate to the initiator is 100:(0.1 to 5), characterized in that the manufacturing method according to claim 1.
4. The temperature of the free radical reaction is 70 to 120°C, preferably 80 to 110°C, and more preferably 90 to 105°C. Preferably, the free radical reaction is carried out in a protective atmosphere. Preferably, the protective atmosphere includes a nitrogen atmosphere and / or an argon atmosphere, characterized in that the manufacturing method according to claim 1.
5. The metal salt includes metal sulfates and / or metal chlorides, and is preferably a metal sulfate. Preferably, the metal in the metal salt includes one or at least two of Al, Ca, Cu, Zn, Fe, and Ti, and more preferably Al. Preferably, the alkaline solution comprises a sodium hydroxide solution and / or a potassium hydroxide solution. Preferably, the temperature of the reaction in step (2) is 20 to 80°C, more preferably 40 to 60°C, as described in claim 1.
6. The flocculant comprises anionic polyacrylamide and / or nonionic polyacrylamide. Preferably, the theoretically obtained mass of the diethylphosphinate metal salt is set to 100%, and the mass of the flocculant is 0.01 to 0.5%. Preferably, the temperature of the mixture in step (3) is 40 to 60°C. Preferably, the number of times the washing in step (3) is ≥ 4, characterized in that the manufacturing method according to claim 1.
7. A polymer additive, wherein the polymer additive is manufactured by a manufacturing method described in any one of claims 1 to 6, and the water-soluble acid value of the polymer additive is ≤0.33 mg KOH / g. The polymer additive comprises, in parts by mass, the following components: 96 to 99.88 parts of diethylphosphinate, 0.1 to 2 parts of ethylbutylphosphinate, 0.01 to 1 part of ethylphosphonate, A polymer additive characterized by comprising 0.01 to 1 part of a monoethylphosphinate.
8. The water-soluble acid value of the polymer additive is 0.1 to 0.3 mg KOH / g. Preferably, the organic acid value of the polymer additive is ≤0.05 mg KOH / g, and more preferably 0.002 to 0.04 mg KOH / g. Preferably, the mass fraction of sulfate in the polymer additive is 100 to 600 ppm, more preferably 110 to 370 ppm. Preferably, the 1% thermal loss temperature of the polymer additive is ≥ 350°C. Preferably, the polymer additive D 50 The particle size is 1 to 100 μm, more preferably 20 to 60 μm, and even more preferably 33 to 39 μm. Preferably, the water content of the polymer additive is 0.01 to 1 wt%, more preferably 0.05 to 0.3 wt%, and even more preferably 0.1 to 0.25 wt%. Preferably, the phosphorus content of the polymer additive is 22 to 25 wt%, more preferably 23 to 24 wt%, as described in claim 7.
9. The use of the polymer additive according to claim 7 in a polymer material, Preferably, the polymer additive is used in the polymer material as a flame retardant.
10. A polymer composition comprising a polymer matrix and the polymer additive described in claim 7, Preferably, the polymer composition comprises, in parts by mass, as a component: Polymer matrix 40 to 99 parts, The polymer additive comprises 5 to 35 parts, Preferably, the polymer matrix comprises a polyamide and / or polyester, characterized in that the polymer composition is characterized by this.
